Genetic diversity of environmental Aspergillus flavus strains in the state of Sao Paulo, Brazil by random amplified polymorphic DNA - Lourenco, Alexandre; Durigon, Edison Luis; Zanotto, Paolo; Gazzinelli Cruz Madeira, Jovita Eugenia; De Almeida, Adriana Palma; Correa, Benedito (Fundaco Oswaldo Cruz, 2007)
Aspergillus flavus is a very important toxigenic fungus that produces aflatoxins, a group of extremely toxic substances to man and animals. Toxigenic fungi can grow in feed crops, such as maize, peanuts, and soybeans, being thus of high concern for public health. There are toxigenic and non-toxigenic A. flavus variants, but the necessary conditions for expressing the toxigenic potential are not fully understood. Therefore, we have studied total-DNA polymorphism from toxigenic and non toxigenic A. flavus strains isolated from maize crops and soil at two geographic locations, 300 km apart, in the Southeast region of Brazil. Total DNA from each A. flavus isolate was extracted and subjected to polymerase chain reaction amplification with five randomic primers through the RAPD (random amplified polymorphic DNA) technique. Phenetic and cladistic analyses of the data, based on bootstrap analyses, led us to conclude that RAPD was not suitable to discriminate toxigenic from non toxigenic strains. But the present results support the use of RAPD for strain characterization, especially for preliminary evaluation over extensive collections.
Keywords: Aspergillus flavus; random amplified polymorphic DNA; phylogeny genetic diversity